2019
DOI: 10.1590/1519-6984.177447
|View full text |Cite
|
Sign up to set email alerts
|

Traditional knowledge and uses of medicinal plants by the inhabitants of the islands of the São Francisco river, Brazil and preliminary analysis of Rhaphiodon echinus (Lamiaceae)

Abstract: This study aimed to carry out an ethnobotanical survey of medicinal plants used by inhabitants of the Rodeadouro Island, Jatoba Island and Massangano Island, located in The Submedium São Francisco River Valley. Also phytochemicals and preliminary pharmacological tests were performed to species most cited by the community. Ethnobotanical data were collected through observation visits and semi-structured interviews with 12 key informants. We calculated the relative importance (RI), the percentage of agreement re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
2
14
0
19
Order By: Relevance
“…It is worth emphasizing that, in the group of individuals who had already been infected by some intestinal parasite (60.5%), 32.2% did not undergo any treatment, whereas, in the group who underwent it (587%), 9.9% used home remedies, such as oil purgative, cocoa liqueur and faith healing. This type of treatment was also reported by other studies which identified that the population used teas, medicinal plants, home medicine and superstition, besides seeing faith healers to treat parasitic infections (Mello et al, 1988;Busato et al, 2015;Pio et al, 2018). Infected individuals who did not undergo treatment mentioned their condition of poverty and the fact that they could not pay for the treatment.…”
Section: Discussionsupporting
confidence: 67%
“…It is worth emphasizing that, in the group of individuals who had already been infected by some intestinal parasite (60.5%), 32.2% did not undergo any treatment, whereas, in the group who underwent it (587%), 9.9% used home remedies, such as oil purgative, cocoa liqueur and faith healing. This type of treatment was also reported by other studies which identified that the population used teas, medicinal plants, home medicine and superstition, besides seeing faith healers to treat parasitic infections (Mello et al, 1988;Busato et al, 2015;Pio et al, 2018). Infected individuals who did not undergo treatment mentioned their condition of poverty and the fact that they could not pay for the treatment.…”
Section: Discussionsupporting
confidence: 67%
“…Family influence was found with regard to this knowledge being passed down from generation to generation, as widely discussed in the scientific literature. 17,18 The most cited plant, worm-seed (Chenopodium ambrosioides L.), is used in popular medicine for a variety of purposes; 19 its antimicrobial activity against strains of M. tuberculosis relieves TB symptoms because it inhibits bacillus growth, 20 and this fact can encourage the incorporation of this species in the care provision for people living with TB. However, under no circumstances whatsoever should it be used to replace treatment proven to lead to cure.…”
Section: Discussionmentioning
confidence: 99%
“…Research, Society and Development, v. 9, n. 7, e585974410, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i7.4410 No Brasil, há uma enorme diversidade de plantas, dentre as quais, encontram-se as plantas da família Lamiaceae que tem distribuição em muitos domínios fitogeográficos do país (Flora do Brasil, 2020). A espécie Rhaphiodon echinus, conhecida popularmente como "betônica", que pertence a esse grupo taxonômico, tem propriedades medicinais e possui em sua composição fitoquímica os flavonoides como um dos produtos do seu metabolismo secundário (PIO et al, 2019).…”
Section: Introductionunclassified